Let's Explore Science - Levit, Joseph (Minneapolis Lerner Publications, 2019)
"What are scientists and what do they do? Learn about these important people."--
Includes bibliographical references (page 24) and index.
Keywords: Science -- Juvenile literature; Scientists -- Juvenile literature; Science; Scientists